The role of the cardiothoracic ratio in the screening of left ventricular hypertrophy in arterial hypertension: a systematic review - Patrycja Matusik; Aleksander Kowal; Amira Bryll; Piotr Sobieraj; Tadeusz J. Popiela; Paweł T. Matusik (Arterial Hypertension)
The presence of hypertensive left ventricular hypertrophy (LVH) is a risk feature associated with both cardiovascular morbidity and mortality. The aim of this review was to evaluate the available data about the diagnostic value of the cardiothoracic ratio (CTR) in the screening for LVH in patients with arterial hypertension. The PubMed and Science Direct databases were searched for terms associated with CTR, LVH, and hypertension. Only articles published in English and available in full text were considered. Finally, 13 papers were selected and analyzed. Hypertensive patients are characterized by increased CTR and left ventricular mass (LVM), when compared to controls. Importantly, mortality among hypertensive patients with a CTR ≥ 0.5 was higher than in those with a CTR < 0.5. In hypertensive patients CTR has varying sensitivities ranging from 16% to 53%, and specificities ranging from 86% to 88.3% for detection of LVH. A combination of CTR ≥ 0.5 with electrocardiographic (ECG) criteria and selected cardiovascular risk factors seems to be a better screening tool for LVH than solely ECG criteria. Thus, providing additional predictive information, especially CTR and clinical data in patients with hypertension, is valuable to improve the diagnostic value of ECG in LVH diagnosis.